Language Service Studies in the Era of AI: Development and Prospects - Cui, Can; Chai, Yue (Journal of Language Service Studies, 2025)
With the rapid advancement of artificial intelligence (AI), the field of language service studies has ushered in a paradigm shift and holds broad development prospects in the AI era. This paper first systematically reviews the global and domestic research progress in AI-driven language services: internationally, scholars focus on the integration of AI technologies with language service workflows, efficiency optimization, and quality evaluation; domestically, research leans toward addressing practical needs such as cross-cultural communication under national strategies and the localization of AI language tools. Subsequently, it examines the current applications of AI in the language service domain, covering key technologies including neural machine translation (NMT) with enhanced contextual adaptation, speech recognition and synthesis supporting real-time multilingual interaction, and large language models (LLMs) enabling intelligent content creation and multi-modal language services. Finally, the paper envisions future research directions such as cross-disciplinary integration of AI, linguistics, and communication, ethical governance of AI language services, and personalized service innovation. It further puts forward pertinent suggestions, including strengthening the construction of multilingual corpus resources, improving the evaluation system for AI-driven language services, and cultivating interdisciplinary talents, so as to promote the high-quality development of the global language service industry.